Research and Progress of Transparent, Flexible Tin Oxide Ultraviolet Photodetector - Qiannan Ye; Xu Zhang; Rihui Yao; Dongxiang Luo; Xianzhe Liu; Wenxin Zou; Chenxiao Guo; Zhuohui Xu; Honglong Ning; Junbiao Peng (Crystals, 2021)
Optical detection is of great significance in various fields such as industry, military, and medical treatment, especially ultraviolet (UV) photodetectors. Moreover, as the demand for wearable devices continues to increase, the UV photodetector, which is one of the most important sensors, has put forward higher requirements for bending resistance, durability, and transparency. Tin oxide (SnO2) has a wide band gap, high ultraviolet exciton gain, etc., and is considered to be an ideal material for preparing UV photodetectors. At present, SnO2-based UV photodetectors have a transparency of more than 70% in the visible light region and also have excellent flexibility of 160% tensile strain. Focusing on SnO2 nanostructures, the article mainly summarizes the progress of SnO2 UV photodetectors in flexibility and transparency in recent years and proposes feasible optimization directions and difficulties.